Effects of Temperature Variation on Behaviour and Growth Performance of African Catfish Clarias gariepinus - Ibrahim, Adamu; Umar, Abubakar M.; Burak, Leatu Nathaniel (Journal of Environmental Microbiology and Toxicology, 2023)
The effect of temperature variation on the behaviour and growth performance of Clarias gariepinus was studied. Temperature has both direct and indirect influence on fisheries and aquaculture. This study was set to evaluate how changes in temperature of the aquatic environment influence the behaviour and growth of Clarias gariepinus as one of the best aquaculture candidates especially in central and western Africa. The fish were subjected to different temperature conditions over a period of eight (8) weeks. Changes in fish behaviour were determined by careful observation of feeding behaviour as well as swimming patterns. Changes in the growth of fish were determined by measuring the weight of the fish and the standard length of the fish accordingly. The outcome of the current study reveals that temperature significantly affects the behaviour and growth performance of Clarias gariepinus. The effect is more significant in the weight than the length of the fish. Temperature values between 20-27 ℃ are more suitable for proper growth and well-being of Clarias gariepinus, any further increase in temperature above 27 ℃ causes a decline in the growth that fish species.